2016
DOI: 10.22456/1679-9216.82863
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in Third Eyelid of Cat

Abstract: Background: The third eyelid neoplasms are uncommon in cats. The squamous cell carcinoma are easily found in head and neck of same specie, although is unusual in eye region. The more commun localization is eyelid and eyeball, being 60 and 15%, respectively. It could bee diagnosed by citology, histopathology, imunohistochemistry and molecular biology. The surgery is more effective treatment, because the tumor can be totally removed and it must available surgical margin. The aim of this study was to report a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
4
0
0
Order By: Relevance
“…As expected, Pan CK, an important epithelial tumor marker, gave a positive reaction in all SCCs, especially in well-differentiated (Rodríguez Guisado et al, 2021). Pan CK immunoreactivity was detected in the cytoplasm of neoplastic epithelial cells, consistent with literature data (Martín de las Mulas et al, 1995;da Conceicao et al, 2016;Sparger et al, 2018;Barbosa et al, 2019). Different researchers reported that they did not find vimentin immunoreactivity in tumoral foci in feline SCCs (Conceicao et al, 2016;Rodríguez Guisado et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As expected, Pan CK, an important epithelial tumor marker, gave a positive reaction in all SCCs, especially in well-differentiated (Rodríguez Guisado et al, 2021). Pan CK immunoreactivity was detected in the cytoplasm of neoplastic epithelial cells, consistent with literature data (Martín de las Mulas et al, 1995;da Conceicao et al, 2016;Sparger et al, 2018;Barbosa et al, 2019). Different researchers reported that they did not find vimentin immunoreactivity in tumoral foci in feline SCCs (Conceicao et al, 2016;Rodríguez Guisado et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, they reported that vimentin-positive staining was observed especially in the connective tissue around the tumoral islands (Barbosa et al, 2019). In the current study, vimentin expression was predominantly detected in mesenchymal cells in the tumor stroma, similar to previous studies (Conceicao et al 2016;Barbosa et al, 2019;Rodríguez Guisado et al, 2021). However, especially in poorly differentiated-SCCs, in addition to mesenchymal cells, epithelial tumor cells were also found to be positive for vimentin expression, albeit in very few numbers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations